Dynamic Incremental Model (MDI) to forecast the SARS-CoV-2 pandemic stabilization period (Research, Society and Development, 2020)
Since the beginning of the year 2020, the world has been experiencing a COVID-19 pandemic, which challenges the public sector to make quick and efficient decisions, as the result is counted in lives. Thus, it is necessary to search for predictive models that support the decision and assist in the understanding of the behavior of the transmissions. In this context, the work aims to present a dynamic model for the daily increase in the number of deaths in order to determine a safety range capable of predicting a stabilization period for these deaths. For this, the model uses exponential and potential curves as limits for analyzing the behavior of the increment curve. The model proved to be efficient when compared to the actual data obtained so far.